A Study of Errors in Bilingual Road, Street and Shop Signs in Iran - Hojati, Alireza (Mediterranean Journal of Social Sciences, 2013)
Bilingual signs are becoming a regular feature of our increasingly globalized and inter-connected world. Oneproblem many bilingual signs suffer from is their having different linguistic errors of varying degrees of seriousness.This study was carried out to investigate different linguistic errors, including grammatical, lexical and spelling, errorsfeaturing in a sample of bilingual signs in Iran. To this end, a number of Farsi-English road, street and shop signswere randomly selected and photographed by the researcher. The pictorial data were then subjected to erroridentificationand error-analysis procedures. Findings suggest that most errors in bilingual Farsi-English signs arelexical ones, though grammatical and other errors also have fairly high frequencies of occurrence in them.